2020
DOI: 10.1108/jec-07-2020-0132
|View full text |Cite
|
Sign up to set email alerts
|

Environmental commitment and environmental sustainability practices of manufacturing small and medium enterprises in Uganda

Abstract: Purpose This study aims to examine the relationship between environmental commitment and environmental sustainability practices of manufacturing small and medium enterprises (SMEs) in Uganda. Design/methodology/approach This study employed a cross-sectional and correlational design using evidence from 106 manufacturing SMEs in Uganda. Data was analyzed through Statistical Package for Social Sciences Version 23. Findings Results show that environmental commitment is a significant predictor of environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 61 publications
(78 reference statements)
2
29
0
Order By: Relevance
“…This is supported by the findings of Orobia et al (2020) that revealed that youth and women entrepreneurs undertake social, environmental and economic practices in their businesses. This is further strengthened by Sendawula et al (2020), who showed that manufacturing small and medium enterprises undertake waste management, ecofriendly packaging, energy efficiency and water…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by the findings of Orobia et al (2020) that revealed that youth and women entrepreneurs undertake social, environmental and economic practices in their businesses. This is further strengthened by Sendawula et al (2020), who showed that manufacturing small and medium enterprises undertake waste management, ecofriendly packaging, energy efficiency and water…”
Section: Discussionmentioning
confidence: 99%
“…Extant evidence shows that most small businesses in Uganda pose both social and environmental challenges (Sendawula et al, 2020;Komakech et al, 2016). Such businesses are in the manufacturing, hotel and restaurant trade sector, for example, small businesses deal in firewood and charcoal to satisfy over 90% of Ugandans who have no access to electricity (UBOS, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, research by Jansson et al (2015) on 450 SMIs in Sweden supported the influence of market orientation, entrepreneurial orientation, and sustainability practices on a commitment to sustainability. Environmental commitment is also an important predictor of the sustainability practices of SMIs in Uganda (Sendawula et al, 2021). Therefore, entrepreneurs need to be directed to seek eco-opportunities to reduce or prevent environmental damage and to utilize waste in products that are environmentally friendly and beneficial to the community.…”
Section: Discussionmentioning
confidence: 99%
“…Considering a vast amount of research undertaken on SPs from various jurisdictions across the globe [43][44][45][46][47], extensive opportunities exist for the uptake and implementation of SPs. In literature, institutional pressures [48][49][50]; green culture [51,52], technological infrastructure [53,45]; technological innovation [54,55,45], environmental commitment [56]; regulatory compliance [57]; Top Management support [53], energy consumption [58], Firm resources [59], organisational capabilities [60] are among the crosscutting drivers for SPs. We note that, the main challenges towards the implementation of SPs relate to; finance and cost of implementation [61]; technological infrastructure [45]; lack of awareness [61]; lack of management commitment [43]; organisational culture [62].…”
Section: Review Of Related Studiesmentioning
confidence: 99%